In-hospital complications of acute right ventricular myocardial infarction - Iqbal, Muhammad Asif; Khan, Nauman; faheem, muhammad; Abdul Rauf, Muhammad; Khan, Sher Bahadur; Shah, Ibrahim; Kibria, Zeeshan; Hafizullah, Mohammad (Journal of Postgraduate Medical Institute, 2013)
Objective: To determine the in-hospital complications of acute right ventricular myocardial infarction(RVMI). Methodology: This study was conducted at Cardiology Department, Lady Reading Hospital, Peshawarfrom May to October 2009. A total of 100 patients with acute RVMI were evaluated for in-hospital complications. Results: Male patients were 77 (77%) and females 23 (23%). Patient's mean age was 59.96+12.3 years withage range 28-82 years. Total in-hospital complication events were 174. In-hospital complications werepresent in 77% patients. Cardiogenic shock was the commonest complication with frequency of 25.8%followed by acute left ventricular failure (LVF) in 17.8% and atrioventricular blocks (AV Blocks) in 14.3%respectively. Re-infarction occurred in 5.7% (10) patients. Thirty eight patients died in our study (21.8%).Among RVMI patients, 65% stayed in-hospital for more than 4 days. Conclusion: Frequency of complications is higher and cardiogenic shock is the most common complicationin acute RVMI patients.